(untitled) - Nguyễn, Duy Bình (Cần Thơ, 2020)
Providing teachers with effective professional development (PD) is seen as a central tenet in the endeavor to enhance education quality and students’ learning outcomes (Kelly, 2006; Desimone, 2009; Dadds, 2014). However, how to evaluate the effect of the existing PD activities and examine their needs for PD activities of EFL high school teacher’s further development have been under-researched in Vietnamese contexts. This study was conducted using both quantitative and qualitative methods of research using questionnaires and interviews. The study involved 80 EFL teachers working at different high schools in a province in the South of Vietnam. In particular, it investigated three main aspects: (1) What forms of PD activities the teachers participated in the past; (2) the impact they perceived these activities had on their practice; and (3) PD activities they expect to attend in the future. The results from the questionnaire and interview revealed that EFL teachers participate in PD activities on an occasional basis. Besides, findings also showed that PD activities have had a positive impact on teachers to reinforce their teaching practice and language proficiency, to plan effective lessons to meet students’ learning needs, and to make positive changes in beliefs about teaching and learning. Concerning future PD activities, the teachers highly perceive the needs for PD activities and prioritize those providing them with opportunities to improve their language skills, learn how to adapt materials appropriately for their students, and understand students’ psychology so that they can better motivate unmotivated students. Based on these findings, implications and recommendations are made for enhancing the quality of PD activities.
Keywords: Anh ngữ,English language; Dạy và học,Study and teaching